2011
DOI: 10.1177/1538574411412827
|View full text |Cite
|
Sign up to set email alerts
|

External Compression of the Superior Mesenteric Artery by the Median Arcuate Ligament

Abstract: The median arcuate ligament can compress the proximal portion of the celiac artery causing symptoms of chronic mesenteric ischemia. This rare condition typically affects young women and often poses a diagnostic challenge. Compression of the superior mesenteric artery (SMA) in addition to the celiac artery represents an unusual variant of median arcuate ligament syndrome (MALS). We present a case of MALS resulting predominantly from external compression of the SMA. Diagnostic and therapeutic options are discuss… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 5 publications
0
9
0
Order By: Relevance
“…During endoscopic CA release, 22 we observed in a few patients that the muscle sling also wraps the SMA, explaining the increase in flow velocity during expiration in these patients. Stein et al 23 also described this in a case report.…”
Section: Discussionmentioning
confidence: 76%
“…During endoscopic CA release, 22 we observed in a few patients that the muscle sling also wraps the SMA, explaining the increase in flow velocity during expiration in these patients. Stein et al 23 also described this in a case report.…”
Section: Discussionmentioning
confidence: 76%
“…These symptoms are usually nonspecific and are easily misdiagnosed as functional dyspepsia, peptic ulcer disease, or gastropathy (1, 2, 3). But our patient showed that MALS might be a cause of recurrent abdominal pain associated with gastric ulcer and profound iron deficiency anemia that this association is relatively uncommon and therefore not well determined.…”
Section: Discussionmentioning
confidence: 99%
“…The character of the abdominal pain is often postprandial and associated with regurgitation of undigested food, and weight loss, all of which are caused by gastric ischemia from impingement of the celiac axis (1, 2, 3). But our patient showed that median arcuate ligament syndrome (MALS) might be a cause of recurrent abdominal pain associated with gastric ulcer and iron deficiency anemia that this association is relatively uncommon and therefore not well determined.…”
Section: Introductionmentioning
confidence: 99%
“…The Dunbar syndrome induced by the celiac trunk compression syndrome (CTCS) also called the median arcuate ligament syndrome (MALS) is a potential clinical entity characterized by a triad comprising epigastric pain, weight loss and postprandial pain with nausea and vomiting [ 5 6 7 8 9 10 ]. These symptoms are believed to be secondary to intermittent ischemia especially during the expiration phase [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…Occasionally, in addition to the CTK the constricting effect of MAL may also manifest on the SMA and rarely on the renal arteries (RAs) [ 8 9 10 ]. If the compression on the SMA is important the development of the typical collaterals is compromised and the indirect and more distal substitution by of the IMA may be required (Figures 5 , 6 , 7 , 8 and 9 ).…”
Section: Introductionmentioning
confidence: 99%